2015
DOI: 10.1016/s2215-0366(15)00376-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of autism spectrum disorder phenomenology in genetic disorders: a systematic review and meta-analysis

Abstract: Cerebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
293
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(311 citation statements)
references
References 25 publications
12
293
0
6
Order By: Relevance
“…Syndromic ASD occurs with Mendelian single gene syndromes, CNV syndromes, and environmental syndromes. Although syndromic ASD has been estimated to account for only 5 to 25 % of all cases of ASD (Adviento et al 2014;de la Torre-Ubieta et al 2016;Jeste and Geschwind 2014), more forms of syndromic ASD continue to be identified (Adviento et al 2014;Richards et al 2015;Roullet et al 2013;Smile et al 2013;Yu and Berry-Kravis 2014;Yuen et al 2015). In addition, syndromic and idiopathic ASD brain impairments have been reported that are similar (Adviento et al 2014;Blackmon 2015;D'Angelo et al 2015;Guilmatre et al 2014;Klusek et al 2015;Sala et al 2015).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 99%
See 1 more Smart Citation
“…Syndromic ASD occurs with Mendelian single gene syndromes, CNV syndromes, and environmental syndromes. Although syndromic ASD has been estimated to account for only 5 to 25 % of all cases of ASD (Adviento et al 2014;de la Torre-Ubieta et al 2016;Jeste and Geschwind 2014), more forms of syndromic ASD continue to be identified (Adviento et al 2014;Richards et al 2015;Roullet et al 2013;Smile et al 2013;Yu and Berry-Kravis 2014;Yuen et al 2015). In addition, syndromic and idiopathic ASD brain impairments have been reported that are similar (Adviento et al 2014;Blackmon 2015;D'Angelo et al 2015;Guilmatre et al 2014;Klusek et al 2015;Sala et al 2015).…”
Section: Does Asd Have Neurobiological Validity?mentioning
confidence: 99%
“…There are many forms of genetic syndromic ASD (Cederlöf et al 2014;Kern et al 2015;Plasschaert et al 2015;Poot 2015;Richards et al 2015). The fact that many different genetic syndromes do yield ASD diagnostic symptoms is the result of locus heterogeneity, wherein different gene variants produce the same phenotype, or the same phenotypic trait or symptom.…”
Section: Genetic Syndromic Asd Has Been Found With Varied Brain Impaimentioning
confidence: 99%
“…Dozens of single genes and chromosomal copy number variants (CNVs)3 increase the relative risk of autism spectrum disorder (ASD) nearly 5–50 times over the current background risk. Yet no single gene or CNV causes ASD in 100% of children who carry the mutation,4 and no single DNA mutation accounts for more than 1–2% of all ASD 5. Specific environmental factors have also been shown to increase the risk of ASD 6, 7.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 In fact, TSC is one of the most commonly occurring single-gene disorders associated with ASD. [4][5][6] Given the high rate of ASD in TSC and the fact that TSC is often diagnosed in utero or in early infancy, 7 TSC has been considered a model system for understanding mechanisms underlying ASD. [8][9][10][11] However, the specific phenotypic profile of ASD in TSC and the extent to which it converges with nonsyndromic ASD (nsASD) has not been well-established.…”
mentioning
confidence: 99%